Assessment of left atrial appendage function and its relationship to pulmonary venous flow pattern by transesophageal echocardiography - Tükek, Tufan; Atilgan, Dursun; Akkaya, Vakur; Kudat, Hasan; Demirel, Seref; Özcan, Mustafa; Korkut, Ferruh (International journal of cardiology, 2001)
We evaluated left atrial appendage function and its relationship to pulmonary venous flow in 53 patients divided into four groups. Group 1 consisted of 10 normal subjects. Group 2 included 15 patients with significant pure mitral stenosis in sinus rhythm. In group 3, there were 13 patients with pure significant mitral stenosis and atrial fibrillation. Group 4 consisted of 15 patients with normal mitral valve and atrial fibrilltion. We found significant decrease in left atrial appendage ejection fraction and maximum emptying flow velocity, velocity time integral of systolic pulmonary venous flow in Groups 2, 3 and 4 in comparison with normal subjects. Systolic pulmonary venous flow velocity was significantly decreased in Groups 3 and 4. There was significant correlation between left atrial appendage ejection fraction and peak emptying flow velocity ( r=0.62, P<0,001). Systolic peak pulmonary venous flow velocity was significantly correlated with left atrial appendage ejection fraction and maximum emptying flow velocity ( r=0.67, P=0,01; r=0.58, P<0,001, respectively). There was also significant correlation between systolic pulmonary venous flow velocity time integral and left atrial appendage ejection fraction ( r=0.66, P=0.001). When normals were excluded from analysis, all the correlations were still significant. We concluded that left atrial appendage is a contractile structure, and that systolic pulmonary venous flow velocity is influenced by left atrial appendage dysfunction. Therefore left atrial appendage function needs to be considered when interpreting Doppler transmitral and systolic pulmonary venous flow patterns.